Chapter 3.3. Digital Intelligence of Managers During Wartime: From Survival to Development - Liashenko, Oleksandra; Plotnichenko, Svitlana; Makhsma, Makhsma; Плотніченко, Світлана Романівна (My University, 2025)
Digital intelligence is a critical competency in the modern world, extending beyond technical skills to support success in business, education, and personal life. The objective of this chapter is to investigate the role of digital intelligence in the managerial activities of higher education institutions (HEIs) in Ukraine under the conditions of full-scale war. The study focuses on the capacities and limitations of HEI managers in adopting and using digital technologies effectively during wartime disruptions. The research methodology combines qualitative analysis with empirical data collection through a nationwide survey of 91 respondents, including academic staff, administrators, and students from Ukrainian HEIs. The survey explored self-assessed digital intelligence, perceptions of colleagues’ digital readiness, the intensity and purposes of digital technology use, and the perceived impact of digital tools on administrative productivity and organizational resilience. The results demonstrate that the majority of respondents rate their digital intelligence as medium or fairly high, and perceive similar levels among their peers. However, a smaller portion report high digital competence, revealing disparities in institutional readiness and skill development. The full-scale war significantly accelerated the adoption of digital tools, with over 80% of respondents indicating intensified use, particularly in teaching, administrative communication, content creation, and external collaboration. The integration of digital tools has been largely perceived as positive, with nearly all respondents recognizing improvements in productivity and efficiency. Nevertheless, respondents also report critical challenges, including information overload, reduced interpersonal communication, increased dependency on technology, and growing concerns over data confidentiality. These issues highlight the psychological and managerial costs of excessive digital engagement, particularly in high-stress wartime environments. The study concludes that digital intelligence is no longer a supplementary skill but a foundational strategic resource in the governance of HEIs. While digital tools have enhanced institutional agility and operational continuity, the uneven distribution of skills and the rise of digital fatigue pose risks to long-term sustainability. To mitigate these effects, HEIs must adopt balanced digital management strategies that prioritize both technological proficiency and human-centered leadership. Digital intelligence enables HEI managers not only to withstand the pressures of war but to lead innovation, promote inclusion, and ensure the continuity and quality of education in times of crisis and beyond.
Keywords: digital intelligence; higher education institutions; digital transformation; management; security